Pengembangan Media Pembelajaran Green Math Berbasis Android Berbantuan Smart Apps Creator (SAC) Pada Materi Koordinat Kartesius D Kelas VIII SMP Negeri 8 Nanga Mahap - Dicky Wiratno; Hartono, Hartono; Desy Susiaty, Utin (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
This study aims to develop interactive learning media based on Android using Smart Apps Creator (SAC) on Cartesian coordinate material. The subjects in this study were 29 students of class VIII of SMP Negeri 8 Nanga Mahap. The research method used is Research and Development (R&D) 4D model consisting of Define, Design, and Develop stages. The instruments used include expert validation sheets, student and teacher response questionnaires, and learning outcome tests. The validation results show that this media is very valid with a validity score of 92.7%. The practicality level of 87.14% indicates a very practical criterion, and the effectiveness level of 82.76% is included in the very effective category. Thus, the developed learning media is suitable for use in the mathematics learning process.